Prediction Model Of Organizational Factors Affecting Medical And Health Care Workers’ Performance At Rsud Jend. Ahmad Yani Metro - Ahmad Farizan Radhitya; Bayu Anggileo Pramesona; Susianti Susianti; Betta Kurniawan; Jhons Fatriyadi Suwandi (Universitas Pahlawan Tuanku Tambusai, 2026)
The performance of medical and health care workers is a crucial indicator of hospital service quality. Performance is influenced by various factors, including individual characteristics, organizational conditions, and psychological and work-environment factors. This study aimed to analyze factors associated with the performance of medical and health care workers at RSUD Jend. Ahmad Yani Metro City and to develop a predictive model of performance based on these factors. This study employed a cross-sectional design and involved 205 medical and health care workers. The variables analyzed included sociodemographic characteristics, work motivation, workload, work stress, leadership style, and remuneration. Data were analyzed using bivariate analysis and multivariate logistic regression. A total of 80% of respondents demonstrated good performance. Bivariate analysis showed significant associations between performance and workload (p < 0.001), work stress (p < 0.001), leadership style (p < 0.001), and remuneration (p < 0.001). The predictive model indicated that respondents exposed to high workload, high work stress, poor leadership style, and low remuneration had a low probability of good performance (5.7%). These findings suggest a cumulative effect of the four factors, which interact and reinforce one another in contributing to decreased performance among medical and health care workers at RSUD Jenderal Ahmad Yani, Metro.